A efetividade das salas de AEEs (Atendimentos Educacionais Especializados) nos anos iniciais das escolas municipais de educação básica de Alegrete/RS - Martins, Cláudia Patrícia Troz Guglilhermi (2024)
Throughout the history of Special Education in Brazil, People with Disabilities (PwD) have gone through various processes until we reached what we now know as School Inclusion. Specialized Educational Services (AEE) came to complement this process of Inclusion. PwD were excluded from both society and the educational context. It was after the 1996 LDB (Law of Guidelines and Bases) that it was mandated that PwD should preferably be enrolled in the regular education system, thus enabling equal opportunities to learn and develop their capacities, skills, and potential. The general objective is to analyze the effective contribution of Specialized Educational Support (AEE) rooms to the progress in learning, access, and retention of students with disabilities in the Early Years of municipal schools in Alegrete. This research presents a historical overview of Special Education and Public Policies for PwD, and collected data through a questionnaire sent to the research participants for later analysis. Therefore, it will have a Quantitative-Qualitative approach, of an Applied Nature, and, in terms of Objective, it is Exploratory, aiming to examine the provision of AEE and identify the opinions, attitudes, and beliefs of the participants regarding Inclusive Education. This study also analyzed how this service is provided and its contribution to the learning, access, and retention of students with disabilities in the Early Years of Municipal Schools in Alegrete, RS. The questionnaire was directed to special education teachers, designated as Specialists by the Department of Education, Sports, and Leisure (SECEL), and to regular classroom teachers in the Early Years, who have students with disabilities receiving Specialized Educational Services (AEE). The questions focused on these teachers' roles in the School Inclusion process. Upon concluding this research, significant concerns were observed among both the specialists and the classroom teachers of students with disabilities. Their primary concerns in the pursuit of quality service converge on the need for support from other external professionals (neuropediatricians, psychiatrists, psychologists, speech therapists, educational psychologists, therapists, and others) and the possibility of increasing the frequency of AEE by offering it in both school shifts (morning/afternoon), as students currently attend AEE only a few times a week. These are simple solutions that could make a significant difference in the effectiveness of AEE services, ultimately benefiting students with disabilities even more.